Previous colonic resection is a risk factor for surgical relapse in Crohn's disease. Issue 2 (February 2019) - Coletta, Marina; Zefelippo, Arianna; Mazza, Stefano; D'Abrosca, Vera; Botti, Fiorenzo; Oreggia, Barbara; Prati, Matteo; Boni, Luigi; Vecchi, Maurizio; Caprioli, Flavio
Abstract: Background: Despite the improvement of medical therapies, nearly half of patients with Crohn's disease require surgery within 10 years after diagnosis. However, intestinal resection is not curative and recurrence may occur. Aims: To evaluate post-surgical outcomes for patients with Crohn's disease in a large monocentric cohort, and to identify variables associated with clinical and surgical relapse. Methods: Patients with Crohn's disease who had surgery for ileal and colonic Crohn's disease between 2004 and 2016 and on at least one-year follow-up following surgery were included. Results: One hundred ninety-three patients were included in the study. Crohn's disease recurrence concerned 53% of patients after a median 56-month (6–158) follow-up and 29% of patients required a second surgical intervention. At logistic regression analysis, active smoking and young age at diagnosis were identified as independent risk factor for post-surgical relapse (p = 0.01), while colonic or ileocolonic resection was recognized as a risk factor for surgical Crohn's disease relapse (p = 0.003). Conclusions: Post-surgery recurrence is frequent for patients with Crohn's disease. Active smoking and young age at diagnosis are risk factors for Crohn's disease recurrence. As compared with patients undergoing small-bowel surgery, patients with colonic resection are proner to relapse requiring a second surgical intervention.